Respuesta :

Here are the steps to find the inverse of an equation:

  1. Change g(x) to y
  2. Switch the positions of x and y
  3. Solve for y
  4. Change y to g^-1(x)

First, let's apply the first two steps:

[tex]g(x)=-4x+1\\y=-4x+1\\x=-4y+1[/tex]

Next, let's solve for y. Firstly, subtract 1 on both sides of the equation:

[tex]x-1=-4y[/tex]

Next, divide both sides by -4:

[tex]\frac{x-1}{-4}=y[/tex]

Now that we have solved for y, apply the last step and your answer will be [tex]g^{-1}(x)=\frac{x-1}{-4}[/tex]